Movements of sub-adult sicklefin lemon sharks Negaprion acutidens in a remote Indian Ocean atoll - Filmalter, John David (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 2012)
The sicklefin lemon shark Negaprion acutidens is a large-bodied (> 3m) coastal shark species, widely distributed in tropical and sub-tropical Indo-Pacific waters. Despite its large size and wide distribution, very little is known about its movement behaviour throughout ontogeny. The primary aim of this thesis was to gain an understanding of the movements of sub-adult N. acutidens, in and around the St. Joseph Atoll, Republic of Seychelles, to facilitate the effective conservation of this vulnerable species. A total of 22 sharks (139 "“ 202 cm TL) were equipped with coded acoustic transmitters and passively monitored using moored acoustic receivers for a period of 20 month from March 2009 to October 2010. The use of passive acoustic telemetry arrays to study behavioural ecology has increased in popularity in recent years and been successfully applied to study a host of teleost and elasmobranch species in a diversity of habitats, ranging from sheltered estuaries to the offshore pelagic environment. However, the practicalities of designing an effective network of receivers to optimally monitor animal movements can be challenging. In this study the receiver array was optimised through a series of incremental steps to achieve an efficient design that allowed for the specific objectives to be addressed. The specific objectives of this study were to i) gain an understanding of the long term space use patterns and site fidelity of sub-adult N. acutidens within degree of use of the St. Joseph Atoll lagoon and surrounding habitats, and ii) investigate their short term behavioural patterns in response to natural rhythmic cycles. The important role the atoll plays in the sub-adult stage of this species was demonstrated by the very low numbers of detections outside the atoll compared to the very large numbers of detections inside the atoll. Over the course of a year the tagged sharks showed a high degree of site fidelity to the atoll, with 79 "“ 100% of the individuals detected during each month and 50% being detected on a near daily basis. This result provides testimony of the nursery role of the atoll and importance of these habitats in the early life history for this species. Individual area use was generally found to be restricted to the eastern part of the atoll incorporating a portion of the central deep lagoon and a nearby adjacent area of the sand flats. The movements of sub-adult N. acutidens on and off of the shallow flats surrounding the central lagoon (likely for foraging) were found to be strongly influenced by the tidal height and the diel cycle. Tagged sharks were found to utilise the flats more regularly when the tidal height was greater than 90 cm and particularly more so during the night and early morning than during daylight times. The combined results of this study expose the vulnerability of this species to rapid local depletion. Similarly, the effectiveness of spatial management measures, such as no-take marine protected areas is highlighted as an efficient tool for the future conservation of this species. In the St. Joseph Atoll in particular, the use of a multi-levelled protection approach, where the eastern portion on the atoll is completely restricted while the remaining area is utilized for non-consumptive tourism activities, could be highly effective. Future research should investigate changes in area use throughout the ontogeny of this species as well improve the understanding of the breeding site fidelity and population size of reproductive females using the St. Joseph Atoll.
Keywords: Silky shark; Silky shark -- Habitat; Sharks -- Amirante Islands (Seychelles)